Mundo do trabalho e cooperativismo: uma análise histórico-crítica das cooperativas de confecção do nordeste brasileiro - Matias, Thalita Eliziário Menezes (2016)
The world of the work is a field of quite complex study, due to several configurations that the work assumes along the history in accordance with the organization of the society. In this form, with sights to approach fact of the world of the work the contemporaneousness, the study open to question was developed supported in the perspective methodological critical of the dialectic historical materialism. This review theory and criticism was aimed at general analyze the Brazilian cooperative, more specifically the cooperatives of confection located in the Northeast region, and its relationship with the new settings in the world of work. For such, the way was passed of understanding the senses and the historical configurations acquired by the work in the society, situating them in a context socioeconomic and politically. Besides, it was looked to investigate the appearance of the cooperatives in the world-wide, Brazilian context and of the Northeast, as well as it will analyze of what it forms the modifications of the world of the work from the process of productive restructuring of the capital, they happened in these organizations. For end, an effort was undertaken in revealing the relation extract and appearance of the cooperatives of production of the Northeast by the light of the state of affairs socioeconomic and Brazilian politics. It was seen that in spite of they presented beginnings as a common advantage, selfmanagement and autonomy, tending when the cooperatives pointing to better conditions of work and equality between the workers, historically, it has if removed more and more from his beginnings. The reality of the cooperatives of production of the Brazilian Northeast points to aspects that reveal the extract of these organizations in confrontation with the appearance emphasized by the legislation and by the organs connected to a cooperativism in Brazil. In fact, it is possible to realize that in most of the times there are spaces demarcated by a bigger exploration of the work, being used by the enterprises like form of outsource his services and too free itself of the labor responsibilities resulted from a relation of contractual one. So, it leaves the workers at the mercy of the informality and the absence of the rights historically conquered by the hard-working class.